2021
DOI: 10.1057/s41269-021-00213-8
|View full text |Cite
|
Sign up to set email alerts
|

Ideological voting for radical right parties in Europe

Abstract: The aim of this research is to examine to what extent the electoral support for radical right parties (RRPs) is driven by ‘policy voting’ and to compare this support with that of centre-right parties. Using the European Election Study 2019, we focus on six party systems: Spain, Italy, France, Germany, Austria, and the United Kingdom. Our analyses reveal that party preferences for RRPs are better explained by policy considerations than by other alternative explanations (e.g. by ‘globalization losers’ or ‘protes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Specifically, the hypotheses raised about the influence of anti-feminism (H1), immigration (H2.2), and authoritarianism (H2.3) prove to be significant. If we look at the standardised beta coefficients of the Linear Regression, we see that the ideological self-placement is by far the variable that most contributes to the explanation of the probability of voting for VOX (beta = 0.343)-in line with what had already been pointed out elsewhere [7][8][9]11]. After it, the variables that most contribute to the explanation of the probability of voting for VOX are the perception of unfairness in feminist ideas (beta = 0.141), agreement with the recentralisation of the State of Autonomies (beta = 0.131), considering a "tougher" government necessary (beta = 0.101), prioritising the fight against crime over rights and freedoms (beta = -0.094), a heavy-handed approach to defend the unity of Spain (beta = 0,092) and immigration as an Andalusian problem (beta = 0.079).…”
Section: Plos Onesupporting
confidence: 75%
See 1 more Smart Citation
“…Specifically, the hypotheses raised about the influence of anti-feminism (H1), immigration (H2.2), and authoritarianism (H2.3) prove to be significant. If we look at the standardised beta coefficients of the Linear Regression, we see that the ideological self-placement is by far the variable that most contributes to the explanation of the probability of voting for VOX (beta = 0.343)-in line with what had already been pointed out elsewhere [7][8][9]11]. After it, the variables that most contribute to the explanation of the probability of voting for VOX are the perception of unfairness in feminist ideas (beta = 0.141), agreement with the recentralisation of the State of Autonomies (beta = 0.131), considering a "tougher" government necessary (beta = 0.101), prioritising the fight against crime over rights and freedoms (beta = -0.094), a heavy-handed approach to defend the unity of Spain (beta = 0,092) and immigration as an Andalusian problem (beta = 0.079).…”
Section: Plos Onesupporting
confidence: 75%
“…In the weeks after the 2018 Andalusian Parliament elections, several analyses published in the press pointed out to the role of different factors explaining the vote for VOX such as antiimmigration attitudes [8][9][10] or the penalty of corruption in the regional government and the rejection of the gender equality and historical memory acts [10]. Also, more recent and complete contributions have demonstrated that opposition to immigration [7,[11][12][13][14], cultural conservatism or attitudes towards gay marriage, as well as the preference for an authoritarian regime [7] or populist attitudes [13] are factors that help driving electoral support for VOX, suggesting some similarities with other Western European radical right-wing parties.…”
Section: The Vote For the Western European Radical Right: The Spanish...mentioning
confidence: 99%
“…The arguments and findings here contribute to a better understanding of the link between anti‐immigration attitudes and support for the populist radical right, particularly from the perspective of policy voting (Kessenich & van der Brug, 2022; Kriesi & Schulte‐Cloos, 2020; Ortiz Barquero et al, 2022). It adds a piece to the puzzle of why the support for PRRPs in Western Europe varies so much within many countries over time (Arzheimer, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…Negative attitudes towards immigrants and multiculturalism are recognized as pivotal factors explaining their enduring presence. Populist radical right party (PRRP) elites raise concerns about immigration and tap into grievances that are prevalent among some voters (Arzheimer, 2009; Elgenius & Rydgren, 2019; Golder, 2016; Kriesi & Schulte‐Cloos, 2020; Mudde, 2007; Norris, 2005; Ortiz Barquero et al, 2022). However, a high number of immigrants or asylum‐seekers does not always, and everywhere, contribute to the electoral fortunes of the populist radical right or the far right (Arzheimer & Carter, 2006; Lonsky, 2021; Lucassen & Lubbers, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research therefore complements demand-side accounts with careful consideration of how the supply side may matter. Crucial aspects of the supply side include the role of leadership (Donovan 2020;Michel et al 2020), public campaign financing (Bichay 2020), party and policy positioning (Barquero et al 2021;Chou et al 2021) and dynamics of party competition (Carter 2002;Mudde 2007). Others have instead focused on how RWPPs have varying willingness and ability to capitalise on the grievances of certain parts of their electorate (Koopmans and Statham 1999;Mudde 2010;Halikiopoulou et al 2013;Vasilopoulou et al 2014).…”
Section: Very High Concernsmentioning
confidence: 99%